Land use planning around protected areas: Case studies in four state parks in the Atlantic forest region of southeastern Brazil - Freitas Lima, Elizete Aparecida Checon [UNESP]; Ranieri, Victor Eduardo Lima (Elsevier, 2018)
The creation of buffer zones (BZs) around protected areas (PAs) has been proposed as a way to conciliate the effective protection of biodiversity and human occupation in surrounding areas. In this study, we seek to discuss some of the challenges to effective buffer zones, focusing our attention on investigating two instruments used for the planning of these areas: the management plan of protected areas, and the municipal master plan. To achieve this, we evaluated the planning of land use around protected areas, as established in the management plans of four protected areas, located in southeastern Brazil, as well as in the master plans of the municipalities covered by these protected areas. We found that these management plans established recommendations rather than specific rules for the use of resources of the buffer zones. Additionally, we verified no uniformity between the master plans on the topic of municipal zoning in the BZs of the PAs studied: only five of the fourteen master plans surveyed delineated a zone around the protected area and defined guidelines for land use consistent with its protection. The results of this study indicate that the use of the buffer zone as an effective strategy for the management of protected areas requires a link between the PA managers and the local government responsible for land use planning, in order to facilitate the articulation between the management plan of the PA and the municipal master plan. Otherwise, the establishment of the buffer zone risks being only a symbolic action, with no practical effect on biodiversity conservation within the protected area.
Keywords: Buffer zone; Management plan; Protected areas